2004
DOI: 10.1159/000081598
|View full text |Cite
|
Sign up to set email alerts
|

Readjustable Transobturator Sling: A Novel Sling Procedure for Male Urinary Incontinence

Abstract: Post-prostatectomy incontinence remains a significant problem for both patients and urologists. We report a case and the surgical technique of successful sling in the treatment of post-prostatectomy urinary incontinence. Sling surgery was performed on a 69-year-old male patient with severe urinary incontinence (6 pads/day) following radical prostatectomy. The procedure was conducted through the transobturator approach using a sling with a silicone foam pad to protect the urethra. At the 7-month follow-up the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The article published in the present issue of the International Braz J Urol by Rapp and co-workers is quite interesting as it seems to show promise that good results can be also achieved passing and fixing the sling through the obturator foramen, as other authors have already shown (6). Although the number of patients studied is still too low and no follow-up is provided yet, this approach must be viewed with great interest because of the transobturator approach used, which could definitely become the standard one, for its ease, reproducibility and low complications rate, provided it will stand the proof of time.…”
Section: Conflict Of Interestmentioning
confidence: 64%
“…The article published in the present issue of the International Braz J Urol by Rapp and co-workers is quite interesting as it seems to show promise that good results can be also achieved passing and fixing the sling through the obturator foramen, as other authors have already shown (6). Although the number of patients studied is still too low and no follow-up is provided yet, this approach must be viewed with great interest because of the transobturator approach used, which could definitely become the standard one, for its ease, reproducibility and low complications rate, provided it will stand the proof of time.…”
Section: Conflict Of Interestmentioning
confidence: 64%
“…This 69-year-old patient suffered from severe SUI after radical prostatectomy for prostate cancer. After placement of a transobturator urethral sling, his urinary pad use decreased from six pads daily to one pad daily at the 7-month follow-up [45].…”
Section: Transobturator Urethral Sling In Menmentioning
confidence: 97%
“…[2][3][4][5][6][7]12 Reported continence rate for the ARGUS Classic is 17%-79% in a maximum follow-up of up to 45 months. In general, onethird of the patients need readjustments.…”
Section: Complicationsmentioning
confidence: 99%